Calcium transport in the thick ascending limb of Henle. Heterogeneity of function in the medullary and cortical segments. - Suki, W N (1980)
Calcium transport was studied in medullary and cortical segments of the thick ascending limb of Henle perfused in vitro. 45Ca was added to the perfusate for measuring lumen-to-bath flux (JlbCa), to the bath for measuring bath-to-lumen flux (JblCa), or to both perfusate and bath for measuring net flux (JnetCa). In the medullary segment JlbCa exceeding JblCa and the efflux:influx coefficient ratio was not different from the value predicted from the observed potential difference (PD). In the cortical segments, however, efflux:influx coefficient ratio was greater than the value predicted from the PD, suggesting that calcium transport in this segment may be active, while it is passive in the medullary segment. Furosemide, which reversibly decreases PD in both cortical and medullary segments, inhibited JlbCa only in the medullary segment. Parathyroid hormone (PTH), on the other hand, had no effect on JnetCa in the medullary segment, but it significantly augmented JnetCa in the cortical segment. These results indicate that calcium transport in the thick ascending limb is heterogeneous. In the medullary segment it is passive, inhibited by furosemide and not influenced by PTH. In the cortical segment, however, calcium transport appears to be active, not inhibited by furosemide and stimulated by PTH.